Model Matematika Pengaruh Lingkungan Terhadap Penyebaran Homoseksual - Afdhal Ahkrizal; Media Rosha (Journal of Mathematics UNP, 2019)
Abstract— Homosexuals are the behaviors of sexual deviations that have occurred in many countries. This homosexual behavior occurs a lot due to negative environmental influences. In Indonesia, homosexual behavior has been caused due to poor social environment such as being too close to same-sex friends, often experiencing a breakup with friends opposite sex, etc. The purpose of the study was to find out the mathematical modelling form of environmental influences on homosexual deployments. This research is a basic study using theoretical methods that analyza theories relating to the influence of the environmental on the spread of homosexual. Based on the results of the reseach of mathematical models of environmental influences on the spread of homosexuals in the form of ordinary differential equation system and stability of the system on this model is asymtotic stable indicating in case of fixed point free from the influence of homsexual behavior. Keywords—Mathematical Model, Homosexual, Environmental Influences.